Trimodal Attention Module for Multimodal Sentiment Analysis (Student Abstract) - Harish, Anirudh Bindiganavale; Sadat, Fatiha (Proceedings of the AAAI Conference on Artificial Intelligence, 2020)
In our research, we propose a new multimodal fusion architecture for the task of sentiment analysis. The 3 modalities used in this paper are text, audio and video. Most of the current methods deal with either a feature level or a decision level fusion. In contrast, we propose an attention-based deep neural network and a training approach to facilitate both feature and decision level fusion. Our network effectively leverages information across all three modalities using a 2 stage fusion process. We test our network on the individual utterance based contextual information extracted from the CMU-MOSI Dataset. A comparison is drawn between the state-of-the-art and our network.